THE IMPACT OF GENERALLY ACCEPTED AUDITING STANDARDS ON THE ROLE OF THE EXTERNAL AUDITOR IN DETECTING AND IDENTIFYING ACCOUNTING VIOLATIONS - Kanar Jassim Mohammed; Prof. Dr. Sabiha Barzan Farhoud (Scholar Express Journals, 2022)
The research aims to shed light on generally accepted auditing standards and external auditing, and to show the relationship between generally accepted auditing standards and the external audit process and its impact on detecting and identifying accounting violations. The research has reached the most important conclusions: the lack of importance of generally accepted standards in the Iraqi environment in order to activate the external audit process to detect and identify accounting violations in the financial statements of government institutions. The research also reached the most important recommendations: the necessity of adopting generally accepted standards in the Iraqi environment in order to activate the external audit process to detect and identify accounting violations in the financial statements of government institutions.
Keywords: External audit; generally accepted auditing standards; accounting irregularities